Carbon material, method for producing carbon material, catalyst, dispersion liquid, electrode, battery, and electrolysis device
By preparing calcined brominated phthalocyanine compounds, the problem of insufficient catalytic activity of existing carbon materials is solved, providing a highly efficient oxygen reduction catalyst suitable for fuel cells, air batteries, and oxygen electrolysis devices.
Patent Information
- Application Number
- CN202480020084.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-06
- Filing Date
- 2024-03-21
- Publication Date
- 2025-11-07
AI Technical Summary
Existing carbon materials have insufficient catalytic activity when used as oxygen reduction catalysts, especially when used as positive electrode catalysts or cathode catalysts in fuel cells and air batteries, making it difficult to meet the requirements for efficient oxygen reduction.
By using calcined products containing brominated phthalocyanine compounds as carbon materials, carbon materials with excellent oxygen reduction activity are prepared through calcination treatment of the phthalocyanine compounds, which can be used to catalyze the four-electron or two-electron reduction reaction of oxygen.
It provides carbon materials with higher catalytic activity, suitable for the positive electrode of fuel cells, air batteries and the cathode of oxygen electrolysis devices, improving oxygen reduction efficiency and catalytic performance.
Smart Images

Figure BDA0005602576220000041 
Figure BDA0005602576220000201
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a carbon material, a method for producing a carbon material, a catalyst, a dispersion liquid, an electrode, a battery, and an electrolytic device. BACKGROUND
[0002] Carbon materials are used for a wide range of applications due to characteristics such as high electrical conductivity, high thermal conductivity, low thermal expansion, light weight, heat resistance, and the like. In recent years, carbon materials containing nitrogen are being studied for use as oxygen reduction catalysts, and for example, the following applications have been proposed: a positive electrode catalyst for a fuel cell and / or an air cell that utilizes the function of a four-electron reduction catalyst that catalyzes a four-electron reduction reaction of oxygen, and a cathode catalyst for an electrolytic device (hydrogen peroxide synthesis device) that utilizes the function of a two-electron reduction catalyst that catalyzes a two-electron reduction reaction of oxygen (for example, refer to Patent Literature 1).
[0003] PRIOR ART DOCUMENTS
[0004] PATENT LITERATURE
[0005] Patent Literature 1: Japanese Patent Application Publication No. 2012-101155
[0006] Patent Literature 2: International Publication No. 2021 / 220495 SUMMARY
[0007] PROBLEMS TO BE SOLVED BY THE INVENTION
[0008] An object of one aspect of the present disclosure is to provide a novel carbon material that can be used for an oxygen reduction catalyst.
[0009] SOLUTION TO PROBLEM
[0010] Several aspects of the present disclosure provide the following [1] to
[15] . [1]
[0012] A carbon material including a sintered product of a phthalocyanine compound having bromine as a substituent. [2]
[0014] The carbon material according to [1], wherein the phthalocyanine compound includes Fe, Co, or Zn as a central metal. [3]
[0016] The carbon material according to [1], wherein the phthalocyanine compound includes Zn as a central metal. [4]
[0018] The carbon material according to any one of [1] to [3], wherein the average number of bromine of the phthalocyanine compound is 4 or more. [5]
[0020] The carbon material according to any one of [1] to [4], wherein the phthalocyanine compound is in powder form,
[0021] The powder composed of the phthalocyanine compound has an average particle diameter of 300 nm or less. [6]
[0023] The carbon material according to any one of [1] to [5], wherein the carbon material has an average particle diameter of 0.01 to 1 μm. [7]
[0025] A method for producing a carbon material according to any one of [1] to [6],
[0026] The production method includes a step of firing a raw material containing the phthalocyanine compound. [8]
[0028] A catalyst for a four-electron reduction reaction of oxygen, the catalyst containing the carbon material according to any one of [1] to [6]. [9]
[0030] A catalyst for a two-electron reduction reaction of oxygen, the catalyst containing the carbon material according to any one of [1] to [6].
[10]
[0032] A dispersion liquid containing the carbon material according to any one of [1] to [6] and a dispersion medium of the carbon material.
[11]
[0034] The dispersion liquid according to
[10] , containing a high-molecular electrolyte.
[12]
[0036] An electrode provided with an electrode catalyst layer containing the carbon material according to any one of [1] to [6].
[13]
[0038] The electrode according to
[12] , wherein the electrode catalyst layer contains a high-molecular electrolyte.
[14]
[0040] A battery provided with the electrode according to
[12] or
[13] .
[15]
[0042] An electrolytic device provided with the electrode according to
[12] or
[13] .
[0043] Effects of the Invention
[0044] According to one aspect of the present disclosure, a novel carbon material that can be used for an oxygen reduction catalyst can be provided. DETAILED DESCRIPTION
[0045] In the present specification, a numerical range represented by "~" indicates a range including the numerical values recited before and after "~" as the minimum value and the maximum value, respectively. In addition, except for the case where it is specifically indicated, the units of the numerical values recited before and after "~" are the same. In the numerical range recited in the present specification in stages, the upper limit value or the lower limit value of a certain stage numerical range can be replaced with the upper limit value or the lower limit value of the numerical range of another stage. In addition, in the numerical range recited in the present specification, the upper limit value or the lower limit value of the numerical range can be replaced with the value shown in the examples (experimental examples). In addition, the upper limit value and the lower limit value recited separately can be arbitrarily combined.
[0046] Hereinafter, a preferred embodiment of the present disclosure will be described. However, the present disclosure is not limited by any of the following embodiments.
[0047] <Carbon material>
[0048] One embodiment of the present application is a carbon material including a sintered product of a phthalocyanine compound having bromine (Br) as a substituent (hereinafter also referred to as "brominated phthalocyanine compound").
[0049] The above-described carbon material exhibits excellent oxygen reduction activity because it includes a sintered product of a brominated phthalocyanine compound. Therefore, the above-described carbon material can be used as a catalyst for a reduction reaction of oxygen (oxygen reduction catalyst), for example, can be used as an electrode catalyst such as a positive electrode catalyst for a fuel cell, an air cell, and the like, a cathode catalyst for an oxygen electrolysis device, and the like. The oxygen reduction activity of the carbon material can be confirmed by the method recited in the examples (experimental examples).
[0050] The sintered product can be a sintered product of one brominated phthalocyanine compound, or can be a sintered product of a plurality of brominated phthalocyanine compounds.
[0051] The brominated phthalocyanine compound has, for example, a structure represented by the following formula (1) or formula (2).
[0052]
[0053] X in formula (1) and formula (2) 1 ~ X 16 Each independently represents a hydrogen atom or a halogen atom. Among them, at least one of X 1 ~ X 16 is a bromine atom.
[0054] M in formula (2) represents a central metal. As the central metal (M), Fe, Co, Ni, Cu, Zn, and the like can be given. Note that phthalocyanine compounds having a central metal are sometimes referred to as "iron phthalocyanine" (central metal: Fe), "cobalt phthalocyanine" (central metal: Co), "copper phthalocyanine" (central metal: Cu), "zinc phthalocyanine" (central metal: Zn), and the like, using a prefix corresponding to the kind of the central metal.
[0055] The brominated phthalocyanine compound can not have the above central metal (M), but in the case where the brominated phthalocyanine compound has the above central metal (M), more excellent oxygen reduction activity is easily obtained. From the viewpoint of easily obtaining further more excellent oxygen reduction activity, the brominated phthalocyanine compound can contain Fe, Co, or Zn as the central metal (M), and from the viewpoint of easily obtaining even more excellent oxygen reduction activity, Zn can be contained.
[0056] The halogen atom can be only a bromine atom, or a combination of a bromine atom and a halogen atom other than a bromine atom (a fluorine atom, a chlorine atom, and an iodine atom). The halogen atom can contain a bromine atom and a chlorine atom.
[0057] From the viewpoint of easily obtaining further more excellent oxygen reduction activity, the phthalocyanine compound having bromine and chlorine as substituents in the brominated phthalocyanine compound, and having Zn as a central metal (brominated chlorinated zinc phthalocyanine), is excellent.
[0058] The average number of bromine atoms in the brominated phthalocyanine compound, that is, the average number of bromine atoms in the brominated phthalocyanine compound (the number of bromine atoms per 1 molecule), is greater than 0, and from the viewpoint of easily obtaining more excellent oxygen reduction activity, can be 4 or more (for example, 4 to 16), can be 5 or more, 8 or more, or 11 or more, or can be 15 or less, or 13 or less.
[0059] From the viewpoint of easily obtaining further more excellent oxygen reduction activity, the average number of chlorine atoms in the brominated phthalocyanine compound, that is, the average number of chlorine atoms in the brominated phthalocyanine compound (the number of chlorine atoms per 1 molecule), can be greater than 0 and 11 or less, can be 0.1 or more, 0.5 or more, or 1 or more, or can be 3 or less, or 2 or less.
[0060] The average number of halogen atoms in the brominated phthalocyanine compound, that is, the average total number of halogen atoms in the brominated phthalocyanine compound (the total number of halogen atoms per 1 molecule), is greater than 0, and from the viewpoint of easily obtaining more excellent oxygen reduction activity, can be 8 to 16, can be 11 or more, or can be 15 or less, or 14 or less.
[0061] The number of the above halogen atoms can be determined, for example, by mass spectrometry using a matrix-assisted laser desorption ionization time-of-flight mass spectrometer (JMS-S3000 manufactured by JEOL Ltd., or the like). Specifically, the number of each halogen atom can be calculated as a relative value per 1 central metal element, based on the mass ratio of the central metal element to each halogen atom in the brominated phthalocyanine compound.
[0062] The brominated phthalocyanine compound is, for example, in the form of a powder. The finer the powder composed of the brominated phthalocyanine compound, the finer the sintered product, and the more excellent the oxygen reduction activity is likely to be. From such a viewpoint, the average particle diameter (average value of the length diameter of primary particles) of the powder composed of the brominated phthalocyanine compound can be 300 nm or less (for example, 10 to 300 nm), 200 nm or less (for example, 10 to 200 nm), 100 nm or less (for example, 10 to 100 nm), 70 nm or less (for example, 10 to 70 nm), 60 nm or less (for example, 10 to 60 nm), or 40 nm or less (for example, 10 to 40 nm), or can be 40 nm or more (for example, 40 to 200 nm) or 70 nm or more (for example, 70 to 200 nm). The average aspect ratio of the powder composed of the brominated phthalocyanine compound can be, for example, 1.0 to 3.0. The powder having such an average particle diameter and average aspect ratio can be produced, for example, by the method described in International Publication No. 2021 / 220495 or the like.
[0063] The carbon material can contain only the above sintered product, or can contain a component other than the above sintered product (other component). From the viewpoint of easily obtaining more excellent oxygen reduction activity, the content of the above sintered product in the carbon material can be 50% by mass or more, or 80% by mass or more or 90% by mass or more, based on the total mass of the carbon material. The content of the above sintered product in the carbon material can be 100% by mass, or 99% by mass or less or 95% by mass or less, based on the total mass of the carbon material.
[0064] The other component can be, for example, a sintered product of a component (component other than the brominated phthalocyanine compound) that can be contained in the raw material to be sintered. However, from the viewpoint of further improving the catalytic activity for the two-electron reduction reaction of oxygen, the carbon material can not contain a sintered product of a compound containing a metal element (particularly, a compound containing at least one metal element selected from the group consisting of Fe, Co, Ni, Cu, Al, and Zn), in addition to the sintered product of the brominated phthalocyanine compound.
[0065] The carbon material can have a shape corresponding to the shape of the sinter. The shape of the carbon material is not particularly limited, and can be, for example, a powder. The median particle diameter of the carbon material can be, for example, 0.01 to 50 μm, or 0.01 to 10 μm. The median particle diameter of the carbon material is the D50 particle diameter measured by a laser diffraction type particle size distribution measuring device equipped with an air flow type dry disperser.
[0066] The average particle diameter of the carbon material can be, for example, 0.01 to 1 μm, or 0.35 μm or less or 0.1 μm or less, or 0.05 μm or more. Among them, when the average particle diameter of the carbon material is 0.01 to 0.35 μm, there is a tendency that more excellent oxygen reduction activity is easily obtained. Note that the average particle diameter is the average particle diameter of primary particles (average primary particle diameter), and can be calculated from the average of 40 primary particles constituting the aggregate on a two-dimensional image, after the sample is ultrasonically dispersed in cyclohexane and photographed with a microscope.
[0067] The carbon material can have fine pores having a size corresponding to the elements other than carbon (nitrogen (N), bromine (Br), chlorine (Cl), metal elements (M), etc.) contained in the above-described brominated phthalocyanine compound. That is, the carbon material can be a porous carbon material (for example, a powder-like porous carbon material).
[0068] The specific surface area (BET specific surface area) of the carbon material can be, for example, 100 m 2 / g or more, or 200 m 2 / g or more, or 300 m 2 / g or more. The specific surface area (BET specific surface area) of the carbon material can be, for example, 2000 m 2 / g or less, or 1500 m 2 / g or less, or 1000 m 2 / g or less. From these viewpoints, the specific surface area (BET specific surface area) of the carbon material can be, for example, 100 to 2000 m 2 / g.
[0069] The carbon material described above is a material mainly containing carbon (C), but can contain the elements other than carbon (nitrogen (N), bromine (Br), chlorine (Cl), metal elements (M), etc.) contained in the above-described brominated phthalocyanine compound.
[0070] The content of carbon (C) in the carbon material can be, for example, 60 mass% or more, or 70 mass% or more, or 80 mass% or more. Note that the content of carbon (C) in the carbon material is the content based on the total mass of the carbon material, and can be measured by CHN elemental analysis using a combustion method.
[0071] The content of nitrogen (N) in the carbon material may be, for example, an amount of 0.300 or less in terms of the number of atoms of nitrogen per 1 in terms of the number of atoms of carbon in the carbon material, or an amount of 0.220 or less or 0.140 or less. The content of nitrogen (N) in the carbon material may be 0 mass ppm, or an amount of 0.005 or more, 0.010 or more, or 0.050 or more in terms of the number of atoms of nitrogen per 1 in terms of the number of atoms of carbon in the carbon material. Note that the number of atoms of carbon and the number of atoms of nitrogen in the carbon material can be determined by X-ray photoelectron spectroscopy (XPS).
[0072] The content of bromine (Br) in the carbon material may be, for example, 100,000 mass ppm or less, or 50,000 mass ppm or less or 20,000 mass ppm or less. The content of bromine (Br) in the carbon material may be 0 mass ppm, or 50 mass ppm or more, 500 mass ppm or more, or 2,000 mass ppm or more. Note that the content of bromine in the carbon material, which is the content with respect to the total mass of the carbon material, can be determined by combustion ion chromatography (CIC).
[0073] The content of chlorine (Cl) in the carbon material may be, for example, 30,000 mass ppm or less, or 10,000 mass ppm or less, 5,000 mass ppm or less, 1,000 mass ppm or less, 500 mass ppm or less, or 100 mass ppm or less. The content of chlorine (Cl) in the carbon material may be 0 mass ppm, or 10 mass ppm or more. Note that the content of chlorine (Cl) in the carbon material, which is the content with respect to the total mass of the carbon material, can be determined by combustion ion chromatography (CIC).
[0074] The content of metal element (M) in the carbon material may be, for example, 20 mass% or less, or 5 mass% or less or 2 mass% or less. The content of metal element (M) in the carbon material may be 0 mass ppm, or 0.005 mass% or more, or 0.1 mass% or more or 1 mass% or more. Note that the content of metal element, which is the content with respect to the total mass of the carbon material, can be determined by inductively coupled plasma-optical emission spectrometry (ICP-OES).
[0075] <Method for producing carbon material>
[0076] Another embodiment of the present disclosure is a method for producing a carbon material, including a step of firing a raw material containing a brominated phthalocyanine compound.
[0077] According to the above method, the carbon material of the above embodiment can be obtained. That is, according to the above method, a novel carbon material useful for an oxygen reduction catalyst can be obtained.
[0078] As the brominated phthalocyanine compound, the above-described brominated phthalocyanine compound can be used, and examples thereof are the same as the above-described examples.
[0079] The raw material can contain only the brominated phthalocyanine compound, or can contain a component other than the brominated phthalocyanine compound (other component). From the viewpoint of easily obtaining more excellent oxygen reduction activity, the content of the brominated phthalocyanine compound in the raw material can be 50% by mass or more, or 80% by mass or more or 90% by mass or more, based on the total mass of the raw material. The content of the brominated phthalocyanine compound in the raw material can be 100% by mass, or 99% by mass or less or 95% by mass or less, based on the total mass of the raw material.
[0080] The other component can be, for example, a phthalocyanine compound having no bromine (Br) as a substituent, or a compound other than a phthalocyanine compound. However, from the viewpoint of further improving the catalytic activity for a two-electron reduction reaction of oxygen, the raw material can not contain a compound containing a metal element (particularly, a compound containing at least one metal element selected from the group consisting of Fe, Co, Ni, Cu, Al, and Zn), in addition to the brominated phthalocyanine compound.
[0081] Specific examples of the other component include metal phthalocyanines such as iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, copper phthalocyanine, aluminum chlorophthalocyanine, and chloro compounds (for example, compounds in which M is Fe, Co, Ni, Cu, Al, or Zn, and X 1 ~X 16 in the above-described formula (2) is a chlorine atom) in which a part of hydrogen atoms of these is replaced with a chlorine atom; tetraphenylporphyrin iron, tris(dibenzoylmethyl)iron, iron sulfate (for example, ferrous sulfate heptahydrate), iron chloride, and ferrous chloride (for example, ferric chloride hexahydrate, ferrous chloride tetrahydrate), and the like.
[0082] As the other component, an organic compound not containing a metal element can also be used. As the organic compound, for example, phenol formaldehyde resin, polyfurfuryl alcohol, furan, furan resin, phenol formaldehyde resin, epoxy resin, polyvinylidene chloride, polythiophene, polysulfone, polyvinyl alcohol, polyvinyl butyral, polyester, polylactic acid, polyether, polyether ether ketone, cellulose, carboxymethyl cellulose, lignin, pitch, polycarbazole, polyacrylic acid, polyacrylate, polymethacrylate, and polymethyl methacrylate, and the like can be listed.
[0083] As the other component, a carbon material such as graphite, activated carbon, amorphous carbon, carbon black, coal, charcoal, coke, carbon nanotube, fullerene, graphene, and the like can also be used.
[0084] The firing temperature of the raw material can be, for example, 600°C or higher, as long as the raw material is carbonized. From the viewpoint of easily obtaining a carbon material having more excellent oxygen reduction activity, the firing temperature of the raw material can be 700°C or higher, or 800°C or higher, or 900°C or higher. From the viewpoint of suppressing the high crystallization of the carbon material, the firing temperature of the raw material can be, for example, 1500°C or lower, or 1200°C or lower, or 1000°C or lower. From these viewpoints, the firing temperature of the raw material can be, for example, 600 to 1500°C, or 700 to 1500°C.
[0085] The firing time of the raw material can be, for example, 0.5 to 6 hours.
[0086] The atmosphere gas at the time of firing can be a non-active gas, an oxidizing gas, a reducing gas, or a mixed gas thereof. As the non-active gas, argon, helium, nitrogen, and the like can be listed. As the oxidizing gas, carbon dioxide and the like can be listed. As the reducing gas, hydrogen, ammonia, and the like can be listed. From the viewpoint of the porosity of the obtained carbon material, the atmosphere gas can contain at least one selected from the group consisting of nitrogen, ammonia, and carbon dioxide. For example, if the specific surface area is increased, a gas containing ammonia can be used. By mixing helium in ammonia, there is a tendency that the total volume of any of mesopores or micropores can be increased. The concentration of ammonia in the gas containing ammonia can be, for example, 0.1 to 50% by volume.
[0087] The firing of the raw material can be performed by one-stage heat treatment, or can be performed by two-stage or more heat treatment. For example, heat treatment can be performed at a temperature lower than 600°C, and then heat treatment can be performed at a temperature of 600°C or higher.
[0088] In the case where the heat treatment is performed in two stages or more, the second stage can be performed in a different atmosphere from the first stage. By setting the gas atmosphere to be different from the first stage, the specific surface area, the total volume of mesopores / micropores, and the like can be easily controlled.
[0089] In one embodiment of the present disclosure, the obtained sintered product can be subjected to washing. That is, the sintered product constituting the carbon material can also be a sintered product after washing. The washing method is not particularly limited, and for example, water washing, acid washing, alkali washing, and the like can be exemplified. From the viewpoint of controlling the content of metal elements, the washing method can be acid washing. As the acid, hydrochloric acid, sulfuric acid, and the like can be exemplified.
[0090] (Catalyst)
[0091] Another embodiment of the present disclosure is a catalyst (for example, an electrode catalyst) containing the carbon material of the above-described embodiment. The catalyst is an oxygen reduction catalyst. The catalyst can be a two-electron reduction catalyst that catalyzes a two-electron reduction reaction of oxygen, or a four-electron reduction catalyst that catalyzes a four-electron reduction reaction of oxygen, but in the case of being used as a two-electron reduction catalyst, there is a tendency to exhibit more excellent catalytic activity. Note that the carbon material of the above-described embodiment exhibits catalytic ability as an oxygen reduction catalyst both in an acidic condition and in an alkaline condition, and thus the oxygen reduction catalyst of the present embodiment can be used both in an acidic condition and in an alkaline condition.
[0092] (Dispersion liquid)
[0093] Another embodiment of the present disclosure is a dispersion liquid containing the carbon material of the above-described embodiment and a dispersion medium of the carbon material. The dispersion liquid is used for formation of an electrode catalyst layer, or the like. That is, one mode of the dispersion liquid is an ink composition for electrode catalyst layer formation.
[0094] As described above, the carbon material of the above-described embodiment is capable of functioning as an oxygen reduction catalyst, and thus the above-described dispersion liquid is useful for formation of an electrode catalyst layer for an oxygen reduction electrode (for example, a positive electrode catalyst layer of a fuel cell, an air cell, or the like, and a cathode catalyst layer of an oxygen electrolysis device).
[0095] As the dispersion medium, a publicly known dispersion medium used when forming an electrode catalyst layer of the above-described battery and / or electrolysis device can be used. For example, water, a lower alcohol (methanol, ethanol, isopropanol, n-propanol, or the like), and a mixture thereof can be used. The content of the dispersion medium in the dispersion liquid can be appropriately adjusted in such a manner that the viscosity of the dispersion liquid becomes a viscosity suitable for a coating device. The content of the dispersion medium in the dispersion liquid can be, for example, 60 to 99.5% by mass based on the total mass of the dispersion liquid.
[0096] The dispersion liquid can be composed only of the carbon material and the dispersion medium, but in addition thereto, a publicly known material used in the formation of the electrode catalyst layer of the above-described battery and / or electrolytic device can also be included. The dispersion liquid can contain, for example, a binder of the carbon material. As the binder, a publicly known organic high molecular compound can be used, and from the viewpoint of being able to form an ion conductive path, a polymer electrolyte can be used. As the polymer electrolyte, for example, a perfluorosulfonic acid polymer such as Nafion (registered trademark) can be cited.
[0097] In the case where the dispersion liquid includes a solid component other than the carbon material (for example, the above-described binder), the content of the carbon material can be 40 to 80% by mass based on the total amount of the solid components in the dispersion liquid. The content of the binder in the dispersion liquid can be 20 to 60% by mass based on the total amount of the solid components in the dispersion liquid. In the case where the dispersion liquid includes a polymer electrolyte, the content of the polymer electrolyte can be 20 to 60% by mass based on the total amount of the solid components in the dispersion liquid. Note that the total amount of the solid components refers to the total amount of the components included in the dispersion liquid other than the dispersion medium.
[0098] The dispersion liquid can also contain a carbon material other than the carbon material of the above-described embodiment. The content of the carbon material other than the carbon material of the above-described embodiment can be 40% by mass or less based on the total amount of all the carbon materials.
[0099] (Electrode)
[0100] Another embodiment of the present disclosure is an electrode provided with an electrode catalyst layer including the carbon material of the above-described embodiment. The electrode is an oxygen reduction electrode, and for example, can be a positive electrode of a fuel cell, an air cell, or the like, or a cathode of an oxygen electrolytic device. The constitution of the electrode other than the electrode catalyst layer can adopt a constitution publicly known with respect to an oxygen reduction electrode in the past. The electrode of one embodiment can further be provided with, for example, a gas diffusion layer, a microporous layer, or the like.
[0101] The electrode catalyst layer can be composed only of the carbon material, or can include a component other than the carbon material depending on its use. As the component other than the carbon material, for example, a binder such as the above-described polymer electrolyte can be cited. The content of the carbon material, the binder, and the polymer electrolyte in the electrode catalyst layer (based on the total mass of the electrode catalyst layer) can be in the same range as the content of the carbon material, the binder, and the polymer electrolyte in the dispersion liquid of the above-described embodiment (based on the total amount of the solid components in the dispersion liquid).
[0102] The above-described electrode catalyst layer can be formed using the dispersion liquid of the above-described embodiment. For example, the above-described electrode catalyst layer can be obtained by applying the dispersion liquid to a support and drying it. The application method is not particularly limited, and for example, a general method such as a bar coater, a spray coater, a screen printer, or the like can be used.
[0103] The electrode described above can also be part of a membrane-electrode assembly (MEA) that constitutes a fuel cell. The MEA has, for example, a positive electrode catalyst layer and a negative electrode catalyst layer, an electrolyte membrane disposed between the positive electrode catalyst layer and the negative electrode catalyst layer, and a pair of gas diffusion layers disposed on the side opposite to the electrolyte membrane side of the positive electrode catalyst layer and the negative electrode catalyst layer, respectively.
[0104] (Battery)
[0105] Another embodiment of the present disclosure is a battery that has the electrode of the above-described embodiment. The battery is, for example, a battery that has the electrode of the above-described embodiment as an oxygen reduction electrode (positive electrode), and can be a fuel cell or an air cell. As the fuel cell, there can be mentioned a solid polymer fuel cell (PEFC), a phosphoric acid fuel cell (PAFC), an alkaline fuel cell (AFC), a molten carbonate fuel cell (MCFC), a solid oxide fuel cell (SOFC), a microbial fuel cell (MFC), and the like. The configuration of the battery other than the positive electrode can employ a configuration conventionally known for fuel cells, air cells, and the like. The battery of one embodiment can be, for example, a fuel cell that has a membrane-electrode assembly (MEA) including the electrode described above.
[0106] (Electrolytic device)
[0107] Another embodiment of the present disclosure is an electrolytic device that has the electrode of the above-described embodiment. The electrolytic device can be an oxygen electrolytic device that has the electrode of the above-described embodiment as an oxygen reduction electrode (cathode). The oxygen electrolytic device synthesizes hydrogen peroxide with the decomposition of oxygen, and can also be referred to as a hydrogen peroxide synthesizing device. The configuration of the battery other than the cathode can employ a configuration conventionally known for oxygen electrolytic devices.
[0108] Examples
[0109] Hereinafter, the present disclosure will be described in more detail using examples, but the present disclosure is not limited to the following examples.
[0110] <Method for measuring the number of halogens>
[0111] The number of halogens (average number of bromine and average number of chlorine) of the materials used in the examples was found by mass spectrometric analysis using JMS-S3000 manufactured by JEOL Ltd.
[0112] <Method for measuring the average particle diameter>
[0113] The average particle diameter (average primary particle diameter) of the material used in the experimental examples was calculated from the average of 40 primary particles constituting the aggregate on a two-dimensional image, after the material was ultrasonically dispersed in cyclohexane and photographed using a microscope.
[0114] <Experimental Example 1>
[0115] As the raw material powder A, C.I. Pigment Green 58 (zinc phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 10 to 60 nm, "BrCl-ZnPc (A)" in Table 1) manufactured by DIC Corporation was prepared. Next, 1.0 g of the raw material powder A was placed in a sintering vessel (CC mark, SSA-S 5B manufactured by Nikka to; alumina 99.6%) disposed in the center of a quartz reaction tube. After nitrogen was flowed at 500 ml / min for 20 minutes to remove air remaining in the tube, the temperature was increased to 600°C (sintering temperature) at 10°C / min under nitrogen flow (500 ml / min) in a tube furnace, and held for 2 hours. Then, after cooling to room temperature under nitrogen flow, the carbon material of the sintered product of the raw material powder A was taken out.
[0116] <Experimental Examples 2 and 3>
[0117] The sintering temperature was changed from 600°C to 800°C or 900°C, and otherwise, the carbon material was produced in the same manner as in Experimental Example 1.
[0118] <Experimental Example 4>
[0119] As the raw material powder B, C.I. Pigment Green 59 (zinc phthalocyanine having bromine and chlorine as substituents, central metal: zinc (Zn), average number of bromine: 8 to 13, average number of chlorine: 0 to 5, average particle diameter: 10 to 60 nm, "BrCl-ZnPc (B)" in Table 1) manufactured by DIC Corporation was prepared. Next, the raw material powder B was used instead of the raw material powder A, and otherwise, the carbon material was produced in the same manner as in Experimental Example 3.
[0120] <Experimental Example 5>
[0121] [Production of Raw Material Powder C]
[0122] In a 300-ml flask, 91 g of sulfuryl chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation), 109 g of aluminum chloride (manufactured by Towa Chemical Co., Ltd.), 15 g of sodium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.), 30 g of iron phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd., phthalocyanine iron (II), product number: P0774, hereinafter the same), and 230 g of bromine (manufactured by FUJIFILM Wako Pure Chemical Corporation) were charged, and the temperature was raised to 130°C. The reaction mixture was kept at 130°C for 4 hours. The reaction mixture (reaction solution) was taken out into water, and the precipitate was allowed to precipitate. The precipitate was filtered, washed with water, and dried, thereby obtaining a crude pigment powder. 12 g of the crude pigment powder, 240 g of Japanese sea salt (manufactured by Nippon Suisan Kaisha, Ltd.), and 35 g of diethylene glycol were charged into a double-arm kneader, and kneaded at 80°C for 18 hours. The obtained mixture was taken out into 700 g of water. After stirring for 1 hour, the mixture was filtered, washed with hot water, dried, and pulverized, thereby obtaining a raw material powder C (iron phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 10 to 60 nm, "BrCl-FePc" in Table 1).
[0123] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder C was used instead of the raw material powder A.
[0124] <Experimental Example 6>
[0125] In a 300-ml flask, 91 g of sulfuryl chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation), 109 g of aluminum chloride (manufactured by Towa Chemical Co., Ltd.), 15 g of sodium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.), 30 g of iron phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd., phthalocyanine iron (II), product number: P0774, hereinafter the same), and 230 g of bromine (manufactured by FUJIFILM Wako Pure Chemical Corporation) were charged, and the temperature was raised to 130°C. The reaction mixture was kept at 130°C for 4 hours. The reaction mixture (reaction solution) was taken out into water, and the precipitate was allowed to precipitate. The precipitate was filtered, washed with water, and dried, thereby obtaining a crude pigment powder. 12 g of the crude pigment powder, 240 g of Japanese sea salt (manufactured by Nippon Suisan Kaisha, Ltd.), and 35 g of diethylene glycol were charged into a double-arm kneader, and kneaded at 80°C for 18 hours. The obtained mixture was taken out into 700 g of water. After stirring for 1 hour, the mixture was filtered, washed with hot water, dried, and pulverized, thereby obtaining a raw material powder C (iron phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 10 to 60 nm, "BrCl-FePc" in Table 1).
[0126] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder D was used instead of the raw material powder A.
[0127] <Experimental Example 7>
[0128] In a 300 ml flask, 91 g of sulfuryl chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation), 109 g of aluminum chloride (manufactured by TOSOH CORPORATION), 15 g of sodium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.), 30 g of copper phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd., copper phthalocyanine (II) (β-form), product number: P1006, hereinafter the same), and 230 g of bromine (manufactured by FUJIFILM Wako Pure Chemical Corporation) were charged, and the temperature was raised to 130°C, and the reaction was carried out at 130°C for 4 hours. The reaction mixture (reaction solution) was taken out into water, and the precipitate was allowed to precipitate, and the precipitate was filtered, and washed with water, and dried, whereby a crude pigment powder was obtained. 12 g of the crude pigment powder, 240 g of Japanese sea salt (manufactured by Nippon Suisan Kaisha, Ltd.), and 35 g of diethylene glycol were charged into a double-arm kneader, and mixed at 80°C for 18 hours, and the obtained mixture was taken out into 700 g of water. After stirring for 1 hour, the mixture was filtered, and washed with hot water, and dried, and pulverized, whereby a raw material powder E (copper phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 10 to 60 nm, "BrCl-CuPc" in Table 1) was obtained.
[0129] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder E was used instead of the raw material powder A.
[0130] <Experimental Example 8>
[0131] In a 150 mL tube-type bottle, 5 g of the raw material powder A and 100 g of propylene glycol monomethyl ether acetate were charged, and ultrasonic treatment was carried out for 8 hours at 31 kHz using a bench-top ultrasonic cleaner W-113MKII manufactured by HAMANO ELECTRONICS CO., LTD. The raw material powder F (zinc phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 210 nm, "BrCl-ZnPc(F)" in Table 1) was obtained by filtration, washing with water, drying, and mortar pulverization.
[0132] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder F was used instead of the raw material powder A.
[0133] <Experimental Example 9>
[0134] In a 150 mL tube-type bottle, 5 g of the raw material powder A and 100 g of cyclohexane were charged, and ultrasonic treatment was carried out for 8 hours at 31 kHz using a bench-top ultrasonic cleaner W-113MKII manufactured by HAMANO ELECTRONICS CO., LTD. The raw material powder G (zinc phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 70 nm, "BrCl-ZnPc(G)" in Table 1) was obtained by filtration, washing with water, drying, and mortar pulverization.
[0135] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder G was used instead of the raw material powder A.
[0136] <Experimental Example 10>
[0137] Into a double-arm kneader, 12 g of the raw material powder A, 240 g of Japanese sea salt (manufactured by Nippon Shokuhin Shokai Co., Ltd.), and 35 g of diethylene glycol were put, and kneaded at 80°C for 18 hours. After the kneading, the obtained mixture was taken out into 700 g of water. After stirring for 1 hour, the mixture was filtered and subjected to hot water washing, drying, and pulverization, thereby obtaining a raw material powder H (zinc phthalocyanine having bromine and chlorine as substituents, average number of bromine: 11 to 16, average number of chlorine: 0 to 5, average particle diameter: 40 nm, "BrCl-ZnPc(H)" in Table 1).
[0138] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder H was used instead of the raw material powder A.
[0139] <Experimental Example 11>
[0140] A carbon material was produced in the same manner as in Experimental Example 3, except that zinc phthalocyanine ("ZnPc" in Table 1, manufactured by DIC Corporation) was used instead of the raw material powder A.
[0141] <Experimental Example 12>
[0142] A carbon material was produced in the same manner as in Experimental Example 3, except that iron phthalocyanine ("FePc" in Table 1) was used instead of the raw material powder A.
[0143] <Experimental Example 13>
[0144] A carbon material was produced in the same manner as in Experimental Example 3, except that cobalt phthalocyanine ("CoPc" in Table 1) was used instead of the raw material powder A.
[0145] <Experimental Example 14>
[0146] A carbon material was produced in the same manner as in Experimental Example 3, except that copper phthalocyanine ("CuPc" in Table 1) was used instead of the raw material powder A.
[0147] <Experimental Example 15>
[0148] Into a 300-ml flask were put 91 g of sulfuryl chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation), 109 g of aluminum chloride (manufactured by TOSOH CORPORATION), 15 g of sodium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.), and 30 g of zinc phthalocyanine (manufactured by DIC Corporation), and the temperature was raised to 130°C. The temperature was maintained at 130°C for 4 hours. The reaction mixture (reaction solution) was taken out into water, and the precipitate was allowed to precipitate. The precipitate was filtered, washed with water, and dried, whereby a crude pigment powder was obtained. Into a double-arm kneader were put 12 g of the crude pigment powder, 240 g of Japanese sea salt (manufactured by Marubeni Nisshoku Co., Ltd.), and 35 g of diethylene glycol, and the mixture was kneaded at 80°C for 18 hours. The obtained mixture was taken out into 700 g of water. After stirring for 1 hour, the mixture was filtered, washed with hot water, dried, and pulverized, whereby a raw material powder I (zinc phthalocyanine having chlorine as a substituent, average number of chlorines: 8 to 13, average particle diameter: 10 to 60 nm, "Cl-ZnPc" in Table 1) was obtained.
[0149] A carbon material was produced in the same manner as in Experimental Example 3, except that the raw material powder I was used instead of the raw material powder A.
[0150] <Experimental Example 16>
[0151] A carbon material was produced in the same manner as in Experimental Example 3, except that a mixed gas of ammonia and helium (ammonia concentration: 1 vol%) was used instead of nitrogen as the flowing gas.
[0152] <Experimental Example 17>
[0153] A carbon material was produced in the same manner as in Experimental Example 3, except that a mixed gas of ammonia and helium (ammonia concentration: 10 vol%) was used instead of nitrogen as the flowing gas.
[0154] <Experimental Example 18>
[0155] A carbon material was produced in the same manner as in Experimental Example 16, except that the carbon material of Experimental Example 3 was used instead of the raw material powder A.
[0156] <Experimental Example 19>
[0157] A carbon material was produced in the same manner as in Experimental Example 18, except that carbon dioxide was used instead of a mixed gas of ammonia and helium as the flowing gas.
[0158] <Analysis>
[0159] (Determination of specific surface area)
[0160] The BET specific surface area of the carbon materials of Experimental Examples 1 to 19 was measured by the nitrogen adsorption method. The measurement was performed using a full-automatic specific surface area measuring device, Macsorb HM model-1208 (manufactured by Mountech Corporation), based on the "determination method of gas adsorption amount by single point method" prescribed in Appendix 2 of Japanese Industrial Standard JIS Z 8830-1990. The results are shown in Table 1.
[0161] (Measurement of average particle diameter)
[0162] The average particle diameter (average primary particle diameter) of the carbon materials of Experimental Examples 1 to 19 was measured. The average particle diameter (average primary particle diameter) was calculated from the average of 40 primary particles constituting the aggregate on a two-dimensional image, after the carbon material was ultrasonically dispersed in cyclohexane and photographed with a microscope. The results are shown in Table 1.
[0163] (Evaluation)
[0164] (Evaluation of oxygen reduction activity)
[0165] [Acidic condition]
[0166] The oxygen reduction activity of the carbon materials of Experimental Examples 1 to 19 under acidic conditions was evaluated using the following method. In addition, as a reference example, the oxygen reduction activity of platinum-supported carbon (trade name: TEC10E10E, manufactured by Tanaka Kikinzoku Kogyo K.K.) that has been used as a catalyst for oxygen reduction electrodes of fuel cells in the past was also evaluated.
[0167] First, 4.1 mg of the carbon material or platinum-supported carbon, 1680 μL of IPA (isopropyl alcohol), 420 μL of ultrapure water, and 30 μL of 5% Nafion (Sigma Aldrich; product number 510211) were measured into a tube-type bottle, and mixed by irradiating ultrasonic waves for 5 minutes, thereby obtaining a dispersion liquid. Four μL of the dispersion liquid was added to the disc portion of a platinum ring GC disc electrode (RRDE) (BAS Inc., product number 012613, outer diameter of ring portion: 7.0 mm, inner diameter of ring portion: 5.0 mm, outer diameter of disc portion: 4.0 mm), and left to stand for about 10 minutes to dry. This was performed a total of 2 times, and a total of 8 μL of the dispersion liquid was applied, thereby obtaining a measurement catalyst electrode (disc electrode area: 0.126 cm 2 , catalyst loading: 123 μg / cm 2 ).
[0168] Next, the oxygen reduction activity of the catalyst electrode for measurement was evaluated using a three-electrode electrochemical cell method with a reference electrode using an Ag / AgCl electrode (BAS Inc.; product number 012167) and a counter electrode using a Pt coil electrode (BAS Inc.; product number 012961). Specifically, first, in a 0.1 M HC104 aqueous solution saturated with nitrogen gas (N2), a range of -0.1 to 0.7 V (vs. Ag / AgCl) was cycled at a scan rate of 100 mV / s to stabilize the measurement system. Next, in a 0.1 M HC104 aqueous solution saturated with oxygen gas (O2), linear sweep voltammetry (LSV) measurement was performed while rotating the catalyst electrode for measurement at 1600 rpm. The LSV measurement was performed by scanning a range of -0.1 to 0.7 V (vs. Ag / AgCl) at 10 mV / s from a high potential to a low potential. The potential of the ring electrode was set to a potential at which hydrogen peroxide could be sufficiently oxidized, i.e., 0.9 V (vs. Ag / AgCl).
[0169] The voltammogram measured with the Ag / AgCl electrode was converted to the RHE reference using the following formula (a) to obtain the disc current value I Disk , the ring current value I Ring , and the reaction start potential E onset at 0.2 V (vs. RHE). In the following formula (a), E observed is the potential on the Ag / AgCl electrode reference, E 0 Ag / AgCl = 0.195, and the pH was 1.0.
[0170] E RHE = E 0 Ag / AgCl + 0.0590 pH + E observed … (a)
[0171] In addition, in order to confirm the proportion of the two-electron reduction reaction (reaction to generate hydrogen peroxide) in the catalyzed oxygen reduction reaction, the hydrogen peroxide generation rate (%H2O2) was obtained based on the following formula (al). Note that, for the capture rate N, the outer radius r1 of the disc portion of the disc electrode, the inner radius r2 of the ring portion of the ring electrode, and the inner radius r3 of the ring portion of the ring electrode were used to calculate based on the following formulas (a2) to (a5).
[0172] • %H2O2 (unit: %) = 2 x I Ring / N / (I Disk + I Ring / N) … (al)
[0173] • N = 1 - F (a / β) + β 2 / 3 [1 - F (a)] - (1 + a + β)2 / 3 {1 - F[(a / β)(1 + a + β)]}...(a2)
[0174] • a = (r2 / r1) 3 -1...(a3)
[0175] • β = (r3 / r1) 3 -(r2 / r1) 3 ...(a4)
[0176] • F(θ) = [3 1 / 2 / (4π)] In[(1 + θ 1 / 3 ) / (1 + θ)] + [3 / (2π)] arctan[(2θ 1 / 3 -1) / 3 1 / 2 ]+ 1 / 4...(a5)
[0177] In this evaluation, the potential at which a reduction current of 0.1 mA / cm 2 was passed was set as the reaction starting potential, and the disk current value I Disk at 0.2 V (vs. RHE) was -1.5 mA / cm 2 In the following, in the case where the reaction starting potential was 0.5 V or more, it was judged that the carbon material had oxygen reduction activity under acidic conditions, and the disk current value I Disk at 0.2 V (vs. RHE) was -4.0 mA / cm 2 In the following, in the case where the reaction starting potential was 0.6 V or more, it was judged that the carbon material had excellent oxygen reduction activity under acidic conditions. In addition, among the carbon materials judged to have oxygen reduction activity, the carbon material having a hydrogen peroxide generation rate (%H2O2) of 40% or more was judged to be particularly useful as a two-electron reduction reaction catalyst, and the carbon material having a hydrogen peroxide generation rate (%H2O2) of 30% or less was judged to be particularly useful as a four-electron reduction reaction catalyst. The results are shown in Table 1.
[0178] [Alkaline conditions]
[0179] Using 0.1 M KOH aqueous solution instead of 0.1 M HCIO4 aqueous solution, changing the range of -0.1 to 0.7 V (vs. Ag / AgCl) to the range of -0.7 to 0.1 V (vs. Ag / AgCl), and setting the potential of the ring electrode to 0.2 V (vs. Ag / AgCl), otherwise, the same operation as in the above-described measurement method under acidic conditions was performed to evaluate the oxygen reduction activity under alkaline conditions of the carbon materials of Experimental Examples 1 to 10 and 16 to 19. Among them, the value of pH for substituting the above-described formula (a) for converting the voltammogram to the RHE reference was 13.
[0180] In this evaluation, the potential at which a reduction current of 0.1 mA / cm2 The potential of the reduction current of the carbon material was set to the reaction starting potential, and the disk current value I at 0.4 V (vs. RHE) was measured. Disk -2.5 mA / cm 2 Hereinafter, in the case where the reaction starting potential was 0.7 V or more, it was judged that the carbon material had oxygen reduction activity under alkaline conditions, and the disk current value I at 0.4 V (vs. RHE) was measured. Disk -3.0 mA / cm 2 Hereinafter, in the case where the reaction starting potential was 0.8 V or more, it was judged that the carbon material had excellent oxygen reduction activity under alkaline conditions. In addition, among the carbon materials judged to have oxygen reduction activity, the carbon material having a hydrogen peroxide generation rate (%H2O2) of 50% or more was judged to be useful as a two-electron reduction reaction catalyst, and the carbon material having a hydrogen peroxide generation rate (%H2O2) of 40% or less was judged to be useful as a four-electron reduction reaction catalyst. The results are shown in Table 1.
[0181] [Table 1]
[0182]
Claims
1. A carbon material comprising a calcined product of a phthalocyanine compound having bromine as a substituent.
2. The carbon material of claim 1, wherein, The phthalocyanine compound contains Fe, Co or Zn as a central metal.
3. The carbon material of claim 1, wherein, The phthalocyanine compound contains Zn as a central metal.
4. The carbon material of claim 1, wherein, The phthalocyanine compound has an average number of bromine of 4 or more.
5. The carbon material of claim 1, wherein, The phthalocyanine compound is in a powder form, The powder composed of the phthalocyanine compound has an average particle diameter of 300 nm or less.
6. The carbon material of claim 1, wherein, The carbon material has an average particle diameter of 0.01 to 1 μm.
7. A method for producing a carbon material according to any one of claims 1 to 6, The production method comprises a step of calcining a raw material containing the phthalocyanine compound.
8. A catalyst for a four-electron reduction reaction of oxygen, comprising the carbon material according to any one of claims 1 to 6.
9. A catalyst for a two-electron reduction reaction of oxygen, comprising the carbon material according to any one of claims 1 to 6.
10. A dispersion liquid containing the carbon material according to any one of claims 1 to 6 and a dispersion medium of the carbon material.
11. The dispersion liquid according to claim 10, containing a high-molecular electrolyte.
12. An electrode comprising an electrode catalyst layer containing the carbon material according to any one of claims 1 to 6.
13. The electrode of claim 12, wherein, The electrode catalyst layer contains a high-molecular electrolyte.
14. A battery comprising the electrode according to claim 12.
15. An electrolytic device comprising the electrode according to claim 12.
Citation Information
Patent Citations
Carbon catalyst and process for production thereof, and electrode and battery using the same
JP2012101155A
Method for producing halogenated zinc phthalocyanine pigment
WO2021220495A1